2019
DOI: 10.1039/c8tx00329g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lunar dust simulant on cardiac function and fibrosis in rats

Abstract: LDS exposure causes systemic inflammatory lesions that affect autonomic function, leading to inflammatory myocardial fibrosis, and its mechanisms involve the mediation of the Nrf2/NOX4 redox balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…At present, research on the health effects of exposure to lunar dust focuses mainly on tissues in direct contact with the dust particles, e.g., the respiratory system, the skin, and the cornea. However, other tissues may be secondarily affected through either the translocation of the dust from the site of initial contact or by adverse effects propagated to distal sites by reactions produced in the primary tissue [55].…”
Section: Cardiovascular Adverse Effectsmentioning
confidence: 99%
“…At present, research on the health effects of exposure to lunar dust focuses mainly on tissues in direct contact with the dust particles, e.g., the respiratory system, the skin, and the cornea. However, other tissues may be secondarily affected through either the translocation of the dust from the site of initial contact or by adverse effects propagated to distal sites by reactions produced in the primary tissue [55].…”
Section: Cardiovascular Adverse Effectsmentioning
confidence: 99%
“…Based on the findings of the Apollo Medical Operations Project, research was commissioned by NASA to investigate pulmonary and ocular toxicity, leading to the creation of the Lunar Airborne Dust Toxicity Advisory Group. 4 Ultimately, research expanded to include cardiac 5 and neurologic 6 studies, but nasal toxicity remains uninvestigated.…”
Section: Apollo Revisitedmentioning
confidence: 99%
“…Due to the scarcity of real lunar dust samples, simulated lunar dust samples are currently used to study the toxicity of lunar dust particles. Studies have shown that exposure of lunar dust simulated samples to the lungs caused local and systemic inflammatory responses in rats, significantly increased parasympathetic nerve activity, aggravated myocardial fibrosis, and ultimately led to myocardial dysfunction and cardiovascular damage 1 . The mechanism of cardiotoxic damage involves inflammatory mechanism, considering that NOX4 may be a potential therapeutic target of lunar dust simulant (LDS) induced myocardial injury 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that exposure of lunar dust simulated samples to the lungs caused local and systemic inflammatory responses in rats, significantly increased parasympathetic nerve activity, aggravated myocardial fibrosis, and ultimately led to myocardial dysfunction and cardiovascular damage 1 . The mechanism of cardiotoxic damage involves inflammatory mechanism, considering that NOX4 may be a potential therapeutic target of lunar dust simulant (LDS) induced myocardial injury 1 . Lam et al studied the pulmonary acute toxicological effects of lunar dust simulants in mice and found that lunar dust was more toxic than titanium dioxide, but less toxic than silica‐containing quartz dust 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation